A Highly Sensitive Immunosensor Based on In Situ Reduced Gold-Chitosan Nanocomposite for Detection of Monosodium L-glutamate - Sharma D.; Devi R.; Jaiswal J.; Dutta H.S.; Khan R.; Dhayal M. (My University, 2025)
Composite of gold nanoparticles (GNP) with chitosan (CS) was synthesized through in situ reduction process enabling uniform distribution of the metal-polymer network. The composite material was coated on a glassy carbon electrode (GCE) to enhance functionalization capability and charge transportation. The transmission electron microscopy (TEM) analysis confirmed an average diameter of GNP ~ 15 nm, whereas UV-Vis spectra showed surface plasmon resonance (SPR) peaks in the range of 520 to 570 nm. XRD spectra of CS-GNP composite film showed a distinct diffraction peak at 38.4° of 2θ value, confirming the face-centered cubic structure of GNP. The interaction of GNP with functional moieties of CS reduces the structural stability of their network. The coating of GNP incorporated CS on GCE enhanced current in cyclic voltammetry and differential pulse voltammetry (DPV) measurements. This electrode was functionalized with NHS-EDC for attaining a higher degree of rabbit anti-glutamate antibodies immobilization. Monosodium L-glutamate (MSG) detection in electrolyte was quantified by measuring a decrease in peak current of DPV due to their interaction with antibodies at the surface of the working electrode. Electrochemical impedance spectroscopy (EIS) measurement also showed a relative increase in impedance with an increase in MSG concentration. The biosensor showed a linear response from 100 pM to 1 μM with a detection sensitivity of the order of ~102 μA/nM. © 2022, The Korean Society for Agricultural Machinery.